A new song - Karon, Jan, 1937- (New York, N.Y. : Penguin Books, 2000)
A retired Episcopal rector accepts an interim post on an island off the coast of North Carolina, where new challenges and adventures await him and his wife.
Originally published: New York, N.Y. : Viking, 1952.
Keywords: Mitford (N.C. : Imaginary place) -- Fiction; City and town life -- North Carolina -- Fiction; Clergy -- North Carolina -- Fiction; North Carolina -- Fiction; Christian fiction; Domestic fiction